POPULATION OF THE KOKAND KHANATE IN HISTORICAL SOURCES AND LITERATURE - Ruzmatova Shakhodat Abdukakhkharovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article uses local sources, archival information, works of foreign tourists and scientists, collections and publications written during the Russian Empire, as well as information given in literature published during the Soviet period and the years of independence on the ethnic composition, location and occupation of the population , living on the territory of the Kokand Khanate. There is a lot of information about the main ethnic groups, their role in the political and social life of the country, their places of residence and their way of life. The article also reflects the processes of arrival and settlement of Uzbek tribes in this region.